2009
DOI: 10.1038/nchembio.243
|View full text |Cite
|
Sign up to set email alerts
|

Moonlighting proteins Hal3 and Vhs3 form a heteromeric PPCDC with Ykl088w in yeast CoA biosynthesis

Abstract: Unlike most other organisms, the essential five-step Coenzyme A biosynthetic pathway has not been fully resolved in yeast. Specifically, the gene(s) encoding the phosphopantothenoylcysteine decarboxylase (PPCDC) activity still remains unidentified.Sequence homology analyses suggest three candidates, namely Ykl088w, Hal3 and Vhs3, as putative PPCDC enzymes in Saccharomyces cerevisiae. Interestingly, Hal3 and Vhs3 have been characterized as negative regulatory subunits of the Ppz1 protein phosphatase. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(109 citation statements)
references
References 50 publications
(54 reference statements)
6
102
1
Order By: Relevance
“…We demonstrated in biochemical assays that, in agreement with the structural conservation of its catalytic domain, the CaPpz1 protein exhibits phosphatase activity. This activity was inhibited by the ScHal3 protein, which is a specific inhibitor of PPZ phosphatases and, at the same time, one of the putative subunits of phosphopantothenoylcysteine decarboxylase (Ruiz et al, 2009). It should be noted that in C. albicans there are two distantly related Hal3 orthologues (orf19.7378 and orf19.3260).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated in biochemical assays that, in agreement with the structural conservation of its catalytic domain, the CaPpz1 protein exhibits phosphatase activity. This activity was inhibited by the ScHal3 protein, which is a specific inhibitor of PPZ phosphatases and, at the same time, one of the putative subunits of phosphopantothenoylcysteine decarboxylase (Ruiz et al, 2009). It should be noted that in C. albicans there are two distantly related Hal3 orthologues (orf19.7378 and orf19.3260).…”
Section: Discussionmentioning
confidence: 99%
“…In the yeast group derived from an ancestor with a duplicated genome (102,103), to which S. cerevisiae belongs, the enzyme would be formed by one Cab3 subunit plus two units of Hal3 and/or Vhs3. In archiascomycetaceous yeasts, to which S. pombe belongs, a homotrimeric protein formed by a Hal3-like protein is found (93). This diversity is conditioned by the structure of the active enzyme.…”
Section: Hal3 From Schizosaccharomyces Pombe Is a Moonlighting Proteimentioning
confidence: 99%
“…The proteins of S. cerevisiae that participate in the decarboxylation of phosphopantothenoyl-L-cysteine to pantotheine-4-phosphate, one of the steps in the biosynthetic pathway of CoA from pantothenate, have been identified in the first decade of the 21st century (93). A heterotrimer formed by the protein Cab3 and two monomers that can be either Hal3 or Vhs3 is required to catalyze that reaction in budding yeast.…”
Section: Hal3 From Schizosaccharomyces Pombe Is a Moonlighting Proteimentioning
confidence: 99%
“…HAL3 is now known to function as a 4′-phosphopantothenoylcysteine (PPC) decarboxylase [133,134,[136][137][138] or a subunit of PPC decarboxylase [139]. However, studies on modified HAL3 and complementary experiments have indicated that its role in promoting the cell cycle is independent of its function in catalyzing PPC [126].…”
Section: Cell Division Pathway Mediated By Hal3mentioning
confidence: 98%